Implementation of Green Accounting in Commercial Banks in Indonesia - Arif, Amirul; Susilowibowo, Joni; Handini, Han Tantri; Farid, Muhammad Miftah (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to analyze the application of green accounting policies in the financial statements of commercial banks in Indonesia and its effect on the company's financial performance.  Method: This quantitative study uses a population of 106 commercial banks in Indonesia with purposive sampling technique, which selects banks having complete annual reports during 2019-2023. Data was obtained through documentation method from annual reports, scientific articles, and green accounting policies. The analysis measures the relationship between Environmental Performance and green accounting disclosure on profitability represented by Return on Assets (ROA).  Results: The results show an R Square value of 0.125, which means that the independent variables (Environmental Performance and Environmental Cost) are only able to explain 12.5% of the variation in ROA, while 87.5% is explained by other factors outside the model. The regression model is significant at the 0.05 level. Specifically, the Environmental Performance variable has a significant positive effect on ROA, while green accounting disclosure has a moderate impact but remains significant.  Novelty: The novelty of the study lies in its focus on the banking sector in Indonesia, which is still minimally explored in the context of green accounting. This study enriches the literature by integrating sustainability theory and stakeholder theory in the Indonesian commercial banking sector. Practically, this study provides insights to banks to improve green accounting practices. This research also opens up opportunities for further studies on the long-term impact of green accounting on financial stability and sustainability.